Materiais lignocelulósicos na compostagem de resíduos da agroindústria do frango de corte - Bernard, Francieli Helena (2015)
The composting process has been used as the main way to stabilize agro-industrial waste from the broiler production chain. These wastes are generated in the run-fattening stage and during the slaughtering and processing of meat, originally inadequate to composting process due to its high levels of nitrogen. The objective of this research was to evaluate different lignocellulosic materials available regionally as a carbon source to be added to the composting process. The lignocellulosic materials were carding cotton waste, pruning of urban trees, sawdust, crushed sugarcane bagasse and crushed napier grass, which mixed with other wastes (reproductive poultry bedding, hatchery waste, flotation sludge, sausage skins and coal from boilers), constituted the treatments. Five windrows were set up and monitored, with C:N ratio of around 30. The windrows were turned twice a week in the first month and once a week in the following months until stabilization, confirmed by the decline of the windrow temperature until it reaches values of room temperature. At every turning, moisture was adjusted to 60%. The time of composting was evaluated, as well as mass reductions and volume (parameters related to optimization of the composting area); losses of N, P and K; concentration of N, P and K and the ratio of humic to fulvic acid - HA / FA that to characterize the agronomic value of the final compost, in addition to monitoring of microbiological parameters such as basal respiration and activity enzymatic β-glucosidase, cellulase, acid and alkaline phosphatase. With the aid of techniques of Multivariate Analysis (Cluster Analysis and Principal Component), it was concluded that the treatment which used the carding cotton waste as a carbon source allowed optimizing the use of composting area and provided the production of a organic compost with greater agronomic value. Regarding the microbiological parameters, these were most intense in the thermophilic phase, being the cellulase activity most accentuated.